investigating the importance of telling short stories in promoting grationty the case of 3ed year EFL students in the university of msila - chafika bouguerra, khedidja zerroukhi (My University, 2019)
Abstract Creativity may have an important role in teaching. As such, teachers have to find ways to trigger learners' creativity in their classes and to enhance creative skills. This can be achieved via the use of different strategies such as short stories. The aim of this study is to scrutinize the role of short stories in developing creativity for English foreign language learners. The study has adopted the exploratory descriptive approach. The sample of the study has been chosen from third year students from the university of M`sila. In order to check the impact of stories in Oral Expression, one questionnaire for teachers and another one for third year students in the University of M’sila were availed. In addition, classroom observations were made and a checklist was used to inspect creativity in Oral Sessions. The outcomes have been measured with qualitative and quantitative methods. The results show that teachers sometimes use storytelling as a means of creativity prompting in their sessions. Moreover, students in M’sila University reckon that short stories can help to strengthen their creative potential. Due to these results, it can be summarised that using stories as a tool in the language classroom is highly beneficial for students as it can promote creativity. For this reason, teachers should profit as much as possible from storytelling in order to promote creativity in their sessions. Résume La créativité est d'une importance vitale dans l'enseignement. En tant que tels, les enseignants doivent trouver des moyens de stimuler la créativité des apprenants dans leurs classes et d'améliorer leurs compétences créatives. Ceci peut être réalisé en utilisant différentes stratégies telles que des nouvelles. Le but de cette étude est d'étudier le rôle des nouvelles dans le développement de la créativité des apprenants de langue étrangère anglophones. L'étude a adopté l'approche descriptive. L'échantillon de l'étude a été choisi parmi les étudiants de troisième année de l'université de M`sila. Pour évaluer l’effet de la narration dans les expressions orales, un questionnaire pour les enseignants et un autre pour les étudiants de troisième année à l’Université de M’sila ont été utilisés. En outre, des observations ont été faites en classe et une liste de contrôle a été utilisée pour contrôler la créativité lors des sessions orales. Les résultats ont été mesurés à l'aide de méthodes qualitatives et quantitatives. Les résultats montrent que les enseignants utilisent parfois les nouvelles comme méthode dans leurs sessions. De plus, les étudiants de l’Université de M’sila estiment que les nouvelles peuvent aider à renforcer leur potentiel de créativité. En raison de ces résultats, on peut résumer que l’utilisation des nouvelles comme outil dans la classe de langue est très bénéfique pour les étudiants car elle peut favoriser la créativité. Pour cette raison, les enseignants devraient tirer profit de la narration pour promouvoir la créativité dans leurs sessions